Genetic assessment of some populations of the medicinal plant Caraway (Carum carvi) using RAPD and ISSR markers - leila fahmideh; Lila Jani pour; Bahman Fazeli-Nasab (فیزیولوژی محیطی گیاهی, 2017)
RAPD and ISSR markers were used in the present study to determine genetic relationship and distance between some populations of Carum carvi. Amplification of genomic DNA all population using RAPD analysis yielded 126 fragments, where TIBMBA02 and TIBMBA08 had the minimum number of fragments (7) and  TIBMBC05 had the maximum number of fragments, (22). ISSR marker yielded 79 fragments, where UBC112 and UBC809had the minimum (1) and maximum (15) fragments, respectively. The Diversity Index value of RAPD primers ranged from 0.8 (TIBMBA02) to 0.94 (TIBMBC05) and also Shanoon Diversity and Nei diversity were 0.57 and 0.38, respectively. In ISSR primers The Diversity Index value ranged from 0.0 (UBC112) to 0.92 (UBC809) and also Shanoon Diversity and Nei diversity were 0.57 and 0.39 respectively. According to ISSR and RAPD markers in combination, maximum genetic similarity (0.48) was observed between Kerman and Jandagh Carum carvi while the minimum similarity (0.115) was observed between Kerman and Neishabour Carum carvi with average 0.315.  Also, cluster analysis segregated all populations into 3 groups according to geographical zone.